A weak ergodic theorem for infinite products of Lipschitzian mappings - Simeon Reich; Alexander J. Zaslavski (Abstract and Applied Analysis)
Let K be a bounded, closed, and convex subset of a Banach space. For a Lipschitzian self-mapping A of K, we denote by Lip(A) its Lipschitz constant. In this paper, we establish a convergence property of infinite products of Lipschitzian self-mappings of K. We consider the set of all sequences At t=1∞ of such self-mappings with the property limsupt→∞Lip(At )≤1. Endowing it with an appropriate topology, we establish a weak ergodic theorem for the infinite products corresponding to generic sequences in this space.